2010
DOI: 10.1007/s00421-010-1630-4
|View full text |Cite
|
Sign up to set email alerts
|

Normobaric hypoxia and sports: the debate continues

Abstract: We have read with interest the recent letter of SanchisGomar et al. (2010), and we basically agree with the authors who concluded that normobaric hypoxia can significantly modify several hematological parameters tested by anti-doping authorities so that anti-doping organizations should take into account the possibility of including normobaric hypoxia among the doping practices at least as a masking method in sports. Nevertheless, we raise several doubts about the fact that two out of three criteria presented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, it is still unknown whether HRC or HRC under hypoxic conditions provides a sufficient stimulus to enhance bone mass. Lippi, Franchini, and Banfi (2011) has speculated that normobaric hypoxia is associated with unfavourable biochemical changes, such as decreased anti-oxidative capacity and increased lipid peroxidation. However, Wiesner et al (2010) have reported that not only the exercise but also hypoxia regulates pathways that are crucial to glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still unknown whether HRC or HRC under hypoxic conditions provides a sufficient stimulus to enhance bone mass. Lippi, Franchini, and Banfi (2011) has speculated that normobaric hypoxia is associated with unfavourable biochemical changes, such as decreased anti-oxidative capacity and increased lipid peroxidation. However, Wiesner et al (2010) have reported that not only the exercise but also hypoxia regulates pathways that are crucial to glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Lippi, Franchini, and Banfi (2011) has speculated that normobaric hypoxia is associated with unfavourable biochemical changes, such as decreased anti‐oxidative capacity and increased lipid peroxidation. However, Wiesner et al.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the blood collection, beside the technical aspects66 67 of the blood draw (which must be performed after allowing a timeout period in a sitting position),1 the timing of the sample collection, the exercise68–70 and the exposure of the athlete to altitude (real or simulated)28 71 are regarded as very important for the stability of haematological markers. Then, the main points to be confirmed are the following:

No training or competition before the last 2 h of the blood test.

Did the athlete train, compete or reside at an altitude greater than 1000 m within the previous 2 weeks?

Did the athlete use any form of altitude simulation (hypoxic tent, mask, etc) during the previous 2 weeks?

Did the athlete receive or donate for any reason blood transfusion the previous 3 months?

…”
Section: Introduction/overviewmentioning
confidence: 99%
“…A sudden reassurance of autologous blood transfusions (i.e., correspondence between donor and receiver) occurred in the 2000s as a consequence of the development of reliable tests for detecting rHuEpo and related substances. The current history of blood doping is hence based on both autologous blood transfusions and novel blood boosting substances, such as continuous erythropoietin receptor activator (CERA) (42) or simulated altitude environments (43) , whereas erythrocyte-mimicking synthetic biomaterial particles (44) and gene doping (45) may represent additional threats for the future (46) .…”
Section: Laboratory Medicine and Doping In Sports Historical And Contmentioning
confidence: 99%